Effectiveness of subconjunctival mitomycin-C compared with subconjunctival triamcinolon acetonide on the recurrence of progresive primary pterygium which underwent Mc Reynolds method - Donny W Chandra Agus Supartoto, Angela Nurini Agni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2007)
Background: The main problem in the management of pterygium is how to diminish the recurrence rateafter surgical treatment. Mitomycin-C an antineoplastic, antifibrotic has been used to prevent recurrencerate of pterygium after excision, however, it correlated with some complications. Subconjunctivaladministration before excision has been proposed to avoid them.Objective: To know the effectivity of subconjunctival of mitomycin-C to decrease the recurrence rate ofprogresive primary pterigyum after Mc Reynold method compared with subconjunctival triamcinolonacetonide.Materials and methods: Randomized clinical trial of 41 progresive primary pterygium in Dr Sardjito Hospitaland Dr Yap Eye Hospital. They were randomly assigned to receive subconjunctival 0.1 ml triamcinolonacetonide or 0.1 ml mitomycin-C and underwent pterygium excision one week later using Mc Reynoldmethod. The follow up period was 6 months to detect any recurrence and complication of the drugsResults: The recurrence rate after subconjunctival mitomycin-C and triamcinolon acetonide was 4.7% and25%, respectively, however the different was not statistically significant (p=0.67). There were nostatistical difference in conjunctival hiperemia, lacrimation and granulation. Blepharospasm was significantlydifferent in seven days. The pain after injection and after excision was statistically different between twotwo groups.Conclusion: The recurrence rate of progressive primary pterygium in triamcinolon acetonide group washigher than mitomycin-C group but there was no statistical difference.Key words : Progressive primary pterygium – mitomycin-C – triamcinolon acetonide – Mc Reynold method